2018
DOI: 10.1111/bjh.15632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in chronic lymphocytic leukaemia associated with expression of CD5, a negative regulator of B‐cell receptor signalling

Abstract: Summary: Chronic lymphocytic leukaemia (CLL) is characterized by expression of CD5 on clonal B cells, and is partly driven by activated B-cell receptor (BCR) signalling. While CD5 is known to be a negative regulator of BCR signalling, it is unknown if variability in CD5 expression exists among patients and whether CLL cell CD5 expression affects CLL clinical outcomes. We assessed the extent to which CD5 expression is correlated with clinical outcomes, and whether this information adds to currently used prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Therefore, CD5 is currently considered one of the characteristic antigens of malignant T cells [8]. In addition, CD5 is also expressed in some B cell malignancies [27, 28]. Clinical trials using anti-CD5 monoclonal antibody have revealed a moderate therapeutic effect in patients with cutaneous T cell lymphomas (CTCLs) or chronic lymphocyte leukemia (CLL) [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CD5 is currently considered one of the characteristic antigens of malignant T cells [8]. In addition, CD5 is also expressed in some B cell malignancies [27, 28]. Clinical trials using anti-CD5 monoclonal antibody have revealed a moderate therapeutic effect in patients with cutaneous T cell lymphomas (CTCLs) or chronic lymphocyte leukemia (CLL) [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic criteria for CD5-negative CLL is an important issue. Several studies have established a diagnosis of CD5-negative CLL where fewer than 5% of leukemic cells demonstrated CD5 expression [ 41 , 42 , 43 , 44 , 45 ]. CD5-negative B-CLL seems to have a different clinical presentation to CD5-positive CLL ( Table 1 ) [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Atypical Immunophenotypementioning
confidence: 99%
“…However, Friedman et al [18] analyzed the correlation between mean fluorescence intensity of the CD5 antigen in a population of leukemic cells and a clinical course of the disease in a group of 423 patients suffering from CLL. It was shown that high MFI rate correlates with longer progression-free survival.…”
Section: Cd5-negative Cllmentioning
confidence: 99%